Target Optimization in Transcranial Direct Current Stimulation - Sadleir, Rosalind; Vannorsdall, Tracy D.; Schretlen, David J.; Gordon, Barry (Frontiers in Psychiatry, 2012)
Transcranial direct current stimulation (tDCS) is an emerging neuromodulation therapy that has been experimentally determined to affect a wide range of behaviors and diseases ranging from motor, cognitive, and memory processes to depression and pain syndromes. The effects of tDCS may be inhibitory or excitatory, depending on the relative polarities of electrodes and their proximity to different brain structures. This distinction is believed to relate to the interaction of current flow with activation thresholds of different neural complexes. tDCS currents are typically applied via a single pair of large electrodes, with one (the active electrode) sited close to brain structures associated with targeted processes. To efficiently direct current toward the areas presumed related to these effects, we devised a method of steering current toward a selected area by reference to a 19-electrode montage applied to a high-resolution finite element model of the head. We used a nonlinear optimization procedure to maximize mean current densities inside the left inferior frontal gyrus, while simultaneously restricting overall current and median current densities within the accumbens. We found that a distributed current pattern could be found that would indeed direct current toward the inferior frontal gyrus in this way, and compared it to other candidate 2-electrode configurations. Further, we found a combination of 4 anterior-posterior electrodes could direct current densities to the accumbens. We conclude that a similar method using multiple electrodes may be a useful means of directing current toward or away from specific brain regions and also of reducing tDCS side effects.